Correction: β-Methyl-δ-valerolactone-containing thermoplastic poly(ester-amide)s: synthesis, mechanical properties, and degradation behavior. Issue 21 (19th May 2021) - Guptill, David M.; Chinta, Bhavani Shankar; Kaicharla, Trinadh; Xu, Shu; Hoye, Thomas R.
Abstract : Correction for 'β-Methyl-δ-valerolactone-containing thermoplastic poly(ester-amide)s: synthesis, mechanical properties, and degradation behavior' by David M. Guptill et al., Polym. Chem., 2021, 12, 1310–1316, DOI: ; 10.1039/D1PY00040C .